ORGANIZING AND CONDUCTING EXPERIMENTAL WORK IN FORMING STUDENTS' INFORMATION COMPETENCE (TAMADDUN NURI JURNALI, 2024)
This article provides feedback on experimental work, the essence of their organization, and research work on the formation of students' information competence.